Pemahaman Agama di Sekolah Dasar Aljama’iyah - Afrahul Fadhila Daulay; Zaimah Zahirah Lubis; Nur Citra Naadirah Br.Tarigan; Hannani Suhailah Wira (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Learning media has three roles, namely as a communicative role, an attention grabber (purposeful role), and a memory/storage role (recording role). (2008) Maheasy et al. The role of more than educational communication is a medium for spreading messages in the process related to learning, increasing student attention or conveying messages that want to be conveyed in each subject. Before the learning process, teachers can create a learning atmosphere to be extraordinary by using teaching materials creatively, innovatively and diversely, such as learning occurs by optimizing the process and as a form of learning success. Another thing in carrying out their duties as educators, teachers must base their steps on religious teachings, as the word of Allah SWT. in Surah An-Nahl verse 44